PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PENGGUNAAN ANGGARAN TERHADAP EFEKTIVITAS PENERAPAN ANGGARAN BERBASIS KINERJA PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN DAERAH PROVINSI SULAWESI UTARA - Sumampow, Melisa; Tinangon, Jantje J.; Tangkuman, Steven (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Performance-based budgeting is a system of preparation and management of local budgets that are oriented towards the achievement of results or performance. Performance-based budgets are influenced by the competence of human resources, rewards, and budget usage. This study aims to determine the influence of competence of human resources, rewards, and budget usage on the effectiveness of performance-based budgeting. The population of this research is 61 staff of civil servants in North Sulawesi Industry and Trade Service Office. This research uses multiple linear regression analysis method with data management using SPSS 22 for windows application aid. The result of the research shows that (1) human resource competence has positive and significant effect on effectiveness of performance based budgeting, (2) reward, positively and significantly influence to effectiveness of performance budgeting applying, (3) budget utilization have positive and significant influence to effectiveness of application performance-based budgeting.Keywords: Human Resource Competence, Reward, Budget Usage, Performance Based Budget